2012
DOI: 10.1587/transinf.e95.d.668
|View full text |Cite
|
Sign up to set email alerts
|

Robust Gait-Based Person Identification against Walking Speed Variations

Abstract: SUMMARYVariations in walking speed have a strong impact on gaitbased person identification. We propose a method that is robust against walking-speed variations. It is based on a combination of cubic higherorder local auto-correlation (CHLAC), gait silhouette-based principal component analysis (GSP), and a statistical framework using hidden Markov models (HMMs). The CHLAC features capture the within-phase spatiotemporal characteristics of each individual, the GSP features retain more shape/phase information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In spite of considerable progress in gait recognition research, invariance to large intra-class variations of gait features is still a challenging problem (e.g., walking speed [33,35,2], viewpoint [23,15,27], clothing [12], and elapsed time [31,29]). Among these features, speed invariance is one of the most important issues because walking speed often varies depending on situation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of considerable progress in gait recognition research, invariance to large intra-class variations of gait features is still a challenging problem (e.g., walking speed [33,35,2], viewpoint [23,15,27], clothing [12], and elapsed time [31,29]). Among these features, speed invariance is one of the most important issues because walking speed often varies depending on situation.…”
Section: Introductionmentioning
confidence: 99%
“…Walking speed change is considered from two aspects: (1) walking speed change between a matching pair of gait image sequences and (2) walking speed change within a gait image sequence. While most studies of speed-invariant gait recognition [33,35,2] consider the first aspect as cross-speed gait recognition, so far very limited attention has been paid to the second aspect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they cannot be changed if the biometric data is counterfeited. In behavioral biometrics, identity is verified through action patterns which can be repeated in a unique manner, such as voice [5] and gait [1]. Behavioral biometrics are less stable since behavior may change due to the physical state of the individual.…”
Section: Introductionmentioning
confidence: 99%
“…However, templates are weak against the natural variations of individual behavioral patterns since they only encode an average representation of observed samples [19]. Statistical models such as Gaussian mixture models (GMM) and hidden Markov models (HMM) have successfully handled variations in individual behavioral patterns [20][21][22][23]. For example, Kale et al [21] showed that HMMs were more robust than templates for gait recognition.…”
Section: Introductionmentioning
confidence: 99%